A Short Note on the Hollock (terminalia Myriocarpa) Plantations of Pasighat (N.E.F.A.) - Chatterjee, S.K. (Indian Forester, 1963)
The hollock (Terminalia myriocarpa) plantations of Pasighat date back to 1929. The type of cover where these plantations were raised originally contained a pure crop of hollock. To begin with such pure hollock forests were attempted to be regenerated by natural means, with artificial assistance, but it was later felt that in order to have uniform stocking over large areas plantation was the best method. Plantations of hollock are raised by direct sowing on wide hoed lines. These lines were originally 22' wide, with a 44' gap between two strips. In subsequent years, the sown strips and intermediate strips were reduced successively to 11'×40'; 11' × 22'; 11' × 11'; 6' × 8' and finally to 4' × 8'. The last spacing gave best growth and ensured the closure of the canopy within a short time. The plantations suffered heavy damage during the earthquake of 1950. The effect of wide initial spacing between lines resulted in stems bending towards the gaps as hollock is an intense light demander. In later plantations, the reduction of the gap between two lines eliminated this defect. The rate of growth of hollock is rapid. Crops have attained 119' height and 4½' girth in about 30 years. Its early growth is also quite fast, a crop height of 50' and crop girth of nearly 2' being attained in 9 years